„transMINT4.0“ – MINT-Bildung stärken durch die Ein- bindung außerschulischer Lernorte am Übergang von der Primar- zur Sekundarstufe - Blumberg, Eva; Wenzel, Annkathrin; Schulze, Jan Roland; Reckmann, Eileen; Puppe, Ricardo; Crummenerl, Lena Luise; Temmen, Katrin (GDSU-Journal)

Neue Perspektiven auf digitalisierungsbezogene MINT-Lehrkräftefortbildungen für den Sachunterricht im Kontext von Schülerlaboren. - Blumberg, Eva; Crummenerl, Lena Luise; Lüsse, Mientje; Brückmann, Maja; Wassing, Janne Lene; Acher, Andres; Sowinski, Ronja; Abels, Simone (Perspektiv(en)wechsel – Sachunterricht neu denken)

Fundamental Patterns – A Taxonomy for Archetype Development in Information Systems - Koldewey, Christian; Avermeyer, Celina Maleen; van der Valk, Hendrik; Zerbin, Julian; Dumitrescu, Roman (Lecture Notes in Computer Science)

Systematic Approach to Early Validation Based on the System Architecture of Advanced Systems in the B2B Sector - Humpert, Lynn; Disselkamp, Jan-Philipp; Cichon, Gerrit; Anacker, Harald; Dumitrescu, Roman (IEEE Engineering Management Review)

Service through communication—Conceptualizing service systems with Luhmann’s systems theory - Beverungen, Daniel; Poeppelbuss, Jens; Hemmrich, Simon; Iqbal, Taskeen (Electronic Markets)
Service research has evolved into an interdisciplinary research field that bridges diverse disciplines, including information systems (IS) and marketing. Nearly two decades ago, the service system concept was introduced as a foundational abstraction in service research, drawing on ideas from the service-dominant logic (S-D logic) of marketing. Despite its widespread adoption in service research, particularly in the IS discipline, the service system concept lacks a solid theoretical foundation. This has resulted in conceptual ambiguity and overlap with related constructs, such as service ecosystems. Moreover, it has largely remained a static analytical lens, insufficiently capturing dynamic service phenomena, including value co-creation and co-destruction, as well as the emergence of institutional arrangements. To address these limitations, we propose Luhmann’s systems theory (LST) as a robust framework for conceptualizing service systems as autopoietic (self-creating) systems, in which communication serves as the fundamental mechanism that drives value co-creation. We derive five theoretical propositions from this re-conceptualization that clarify conceptual ambiguity and allow researchers to explore dynamic service phenomena in greater depth. Given LST’s general approach, our conceptualization provides a theoretically grounded, interdisciplinary foundation for advancing service research.
Keywords: Service system; Service ecosystem; Systems theory; Service research

Enhancing Product Management Performance through Digitalization: Advantages, Challenges, Design Fields - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Annual Hawaii International Conference on System Sciences)

Towards a digital factory twin: systematization of material flow simulation use cases - Kattenstroth, Fiona; Kranz, Michael; Hunger, Sebastian; Withot, Dennis; Hovemann, Aschot; Dumitrescu, Roman (Procedia Computer Science)

Identifying Cost Drivers in Circular Business Model Planning: Insights from an Explorative Interview Study - Rasor, Anja; Petzke, Lisa Irene; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Design Principles and Process Model for Planning Data Analytics in Product Management - Grigoryan, Khoren; Bauer, Eliana; Fichtler, Timm; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Bridging chemistry and Gaussian boson sampling: a photonic hierarchy of approximations for molecular vibronic spectra - Eickmann, Jan-Lucas; Luo, Kai-Hong; Roiz, Mikhail; Lammers, Jonas; Atzeni, Simone; Pandey, Cheeranjiv; Lütkewitte, Florian; Shirazi, Reza G.; Schlue, Fabian; Brecht, Benjamin; Rybkin, Vladimir V.; Stefszky, Michael; et al. (npj Quantum Information)
Simulating vibronic spectra is a central task in physical chemistry, offering insight into important properties of molecules. Recently, it has been experimentally demonstrated that photonic platforms based on Gaussian boson sampling (GBS) are capable of performing these simulations. However, whether an actual GBS approach is required depends on the molecule under investigation. To develop a better understanding on the requirements for simulating vibronic spectra, we explore connections between theoretical approximations in physical chemistry and their photonic counterparts. Mapping these approximations into photonics, we show that for certain molecules the GBS approach is unnecessary. We place special emphasis on the linear coupling approximation, which in photonics corresponds to sampling from multiple coherent states. By implementing this approach in experiments, we demonstrate improved similarities over previously reported GBS results for formic acid and identify the particular attributes that a molecule must exhibit for this, and other approximations, to be valid. These results highlight the importance in forming deeper connections between traditional methods and photonic approaches.

Developing AI Literacy of Novice Adult Learners Outside of Formal Education Settings – a Prototype - Rinkowski, Alexander; Kundisch, Dennis (Design for Better Futures: Beyond the Science of the Artificial. Prototypes and Research-in-Progress)

Organizational Capabilities for Implementing R-Strategies in Circular Value Networks - Petzke, Lisa Irene; Vehmeyer, Julia Marie; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Knowledge Gaps in Circular Product Development: A Systematic Literature Review of the Manufacturing Industry - Twardzik, Jan Luca; Humpert, Lynn; Cichon, Gerrit; Dumitrescu, Roman (Lecture Notes in Mechanical Engineering)

Unleashing the Potential of the Digital Product Passport in Engineering: A Structured Map for Sustainable Product Design - Trienens, Malte; Busch, Vanessa; Wyrwich, Fabian; Hovemann, Aschot; Dumitrescu, Roman (Procedia CIRP)

The fellowship of the circle: Barriers to establishing partnerships for circular value creation - Vehmeyer, Julia Marie; Petzke, Lisa Irene; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Fields of Action of a Digital Engineering Transformation Framework - Wyrwich, Fabian; Trienens, Malte; Hovemann, Aschot; Dumitrescu, Roman (2025 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))

Impact of vehicle scheduling and strategic transition planning on zero-emission bus systems - Stumpe, Miriam; Rößler-von Saß, David; Kliewer, Natalia; Schryen, Guido (Transportation Research Interdisciplinary Perspectives)
This paper presents a holistic framework for the transition from diesel to electric bus networks, crucial for meeting EU regulations targeting 100% zero-emission urban buses by 2035. We employ a two-phase solution framework: in phase 1, we solve the Charging Location and Electric Vehicle Scheduling Problem to generate vehicle schedules that are feasible for electric operation; in phase 2, these schedules serve as input to a multi-period transition planning model that minimizes the total cost of ownership while determining fleet replacement and charging infrastructure deployment. Our experiments show that schedules obtained from solving the integrated charging location and vehicle scheduling problem significantly outperform traditional methods, resulting in lower total cost of ownership. Additionally, transition plans reduce local emissions by up to 85% compared to a diesel-only scenario. We find that vehicle rotations with long distances and sufficient idle time are prioritized for electrification, enabling earlier emission reductions and cost savings. This highlights the importance of adopting vehicle scheduling tailored for electric buses, rather than relying on legacy diesel schedules.
Keywords: Electric bus; Multi-period planning; Electric vehicle scheduling; Charging infrastructure; Fleet replacement

Theorising Forward: Positioning Deductive Elaboration in the Information Systems Research Repertoire - Paré, Guy; Wagner, Gerit; Tate, Mary; Schryen, Guido; Templier, Mathieu (European Journal of Information Systems)

Dimensions of Heuristic Use in Mathematical Problem Solving: Evidence from Early Secondary School Students - Herold-Blasius, Raja; Kleinschmidt, Hannah; Ziller, Conrad (Journal für Mathematik-Didaktik)
Mathematical problem solving is a highly complex competence that needs to be supported throughout the learning process. This study examines the role of problem-solving heuristics among 73 sixth-grade students in a German secondary school (Gesamtschule). Specifically, we focus on the empirical relationship between the occurrence of heuristics, their suitability, and application, as well as their contribution to problem-solving success. To this end, we developed a heuristic training that introduced strategy keys (heuristic aid cards) accompanied by explanatory videos. By leveraging variations in the successful application of the heuristics between students and across multiple sessions (73 students in 4 training situations and 3 problems in a final test), we discover from regression models with student and task-fixed effects that a successful use of heuristics (i.e., an heuristic occurred, that heuristic had a high suitability regarding the problem, and it was applied correctly) leads to more successful mathematical problem solving. Regarding the underlying mechanism, we find that all dimensions of heuristic use (occurrence, suitability, and application of heuristics) are positively related to problem-solving success. When comparing the predictive capacity of all three aspects, we identified the correct application of heuristics as particularly conducive for better problem-solving success. In comparing the group of students with high to those with low initial math competence, we find no significant differences in the relationship between heuristic use and problemsolving success across achievement groups. Our results emphasize the crucial role of heuristic application in mathematical problem solving, which generally benefits students regardless of their overall math competence.

Numerical Analysis of the Influence of a Movable Die on Joint Formation in Versatile Self-Piercing Riveting - Kaimann, Pia Katharina; Bobbert, Mathias; Meschut, Gerson (Materials Science Forum)
Self-piercing riveting (SPR) is a well-established joining technique in lightweight construction, as it enables the joining of different materials without requiring pre-drilling. However, the necessary adaptation of the rivet-die combination to the respective material and thickness combinations requires a large number of specific tool sets, which significantly limits the process's flexibility. To overcome these limitations, the versatile self-piercing riveting (V-SPR) was developed, which features enhanced punch actuation in combination with a multi-range-capable rivet . In this context, the concept of a movable die was introduced, which enables an extended process window and adaptable joint formation. Kappe et al. presented initial studies demonstrating the potential of this approach . However, a detailed numerical understanding of the underlying mechanisms remains lacking. This paper presents a numerical analysis of V-SPR with a movable die using a finite element (FE) model. The model includes deformable rivets, sheet metal materials and a kinematically controlled die with adjustable movement. A parameter study was conducted to analyse the influence of die movement on the material flow of the rivet and sheets, as well as joint formation. The simulations were validated using selected experimental data. The goal is to compare the joint geometries achieved with fixed and moving dies and expand the process windows of VSPR. The results demonstrate that the movable-die concept significantly enhances the material flow of both the sheets and the rivet, resulting in a noticeably larger and more reliable interlock than what is achievable with V-SPR using a fixed die. The numerical analyses support the observations reported by Kappe et al. and extend them by providing a quantitative description of how die displacement influences the resulting interlock size. Moreover, the ability to precisely control the die movement makes it possible to join challenging sheet-metal combinations that are difficult to process with conventional setups, particularly in cases involving thicker sheet materials.